If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -13 + 6x + 6x = 33 Combine like terms: 6x + 6x = 12x -13 + 12x = 33 Solving -13 + 12x = 33 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '13' to each side of the equation. -13 + 13 + 12x = 33 + 13 Combine like terms: -13 + 13 = 0 0 + 12x = 33 + 13 12x = 33 + 13 Combine like terms: 33 + 13 = 46 12x = 46 Divide each side by '12'. x = 3.833333333 Simplifying x = 3.833333333
| -11x+15x=22+11 | | 1=-2x | | Y=100-(1/8)x | | 2k^2+7k-4=0 | | 10x-12x+8=16 | | -8(x+5)+9=-31 | | 7=6m-4+3 | | 7/8-1/6+2/3 | | 11x^2-36x+9=0 | | -4x+16x-6=44 | | 126/14 | | 0.75x+3.50=32.75 | | 2(4x+6)=-32+28 | | 4x+8=7x-25 | | 0.75x+3.50=17.00 | | 4x-1/5 | | 4g-g-5=3 | | 6(x-8)=5x-6 | | 3/4x4/5 | | 0.50y+10x=1044 | | 0.75x+3.50=7.00 | | 8(w-3)=7w-2 | | 6x-7+x=7x+4-2x | | 6x-3y=30 | | 18x+10-14x=-34 | | 9x-7=28+4x | | m/4-4.6=-3.1 | | 18=r(2) | | X=5.6 | | 7(1)-8y=56 | | 5=4(3y-2) | | 11x-18=3+8x |